2006
DOI: 10.1111/j.0303-6987.2006.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

t(14;18)(q32;q21) involving IGH and MALT1 is uncommon in cutaneous MALT lymphomas and primary cutaneous diffuse large B‐cell lymphomas

Abstract: This study demonstrates that translocations involving MALT1, including IGH/MALT1, are uncommon in cutaneous MALT lymphomas and primary cutaneous DLBCL. Other translocations involving IGH also are not involved in the pathogenesis of at least most cutaneous MALT lymphomas. In contrast, primary cutaneous DLBCL may contain one of several IGH translocations in a minority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…83 MALT-lymphoma associated translocations have not been described. 81,84,85 but clonality can usually be shown by PCR. 75,76 PCMZL is an indolent disease with a 5-year disease-specific survival of over 95%.…”
Section: Primary Cutaneous Marginal Zone Lymphomamentioning
confidence: 99%
“…83 MALT-lymphoma associated translocations have not been described. 81,84,85 but clonality can usually be shown by PCR. 75,76 PCMZL is an indolent disease with a 5-year disease-specific survival of over 95%.…”
Section: Primary Cutaneous Marginal Zone Lymphomamentioning
confidence: 99%
“…About 5% of intestinal and pulmonary MZBCLs harbor the t(1;14) ( Table 2). [128][129][130][131]142,143 More recently, three novel IgH translocations in non-gastric MZBCL involving ODZ2, CNN3 and JMJD2C have been described, of which ODZ2 and JMJD2C were found recurrently. 144 The t(11;18) is present in ~40% of pulmonary-and iñ 20% of gastric-MZBCLs and is virtually absent in MZBCLs of the salivary gland (Table 2).…”
Section: Genetic Alterations In Low-and High-grade Extranodal Marginamentioning
confidence: 99%
“…Streubel et al 12 reported API2-MALT1 translocation in 4 of 51 cases, but others, including the cases reported here, did not detect any cases with this abnormality. 9,11,[13][14][15][16] The IGH-MALT1 translocation has been reported in 7/51 cases 12 and 3/12 cases. 15 However, it was absent in several other studies.…”
Section: Primary Cutaneous Marginal Zone B-cell Lymphoma H Takino Et Almentioning
confidence: 98%
“…15 However, it was absent in several other studies. 13,14 The explanation for these variable results remains unknown. In MALT lymphomas, an association between nuclear BCL10 expression and the presence of API2-MALT1 fusion has been suggested.…”
Section: Primary Cutaneous Marginal Zone B-cell Lymphoma H Takino Et Almentioning
confidence: 99%
See 1 more Smart Citation